Female Migration and Native Marital Stability: Insights from Italy - Daniele Vignoli; Alessandra Venturini; Elena Pirani (Institute for the Study of Labor (IZA), 2015)
In this paper, we argue that the size and the composition of the female migrant population in a given area can affect the marital stability of natives. We take Italy as a case-study and we offer discrete-time event history models predicting marital disruption on data from the nationally – representative 2009 Family and Social Subjects survey. We found that the increasing presence of first mover migrant women (coming from Latin America and Eastern Europe) is associated with higher separation risks among natives, especially for couples with lower human capital. Our findings add to our understanding of family formation and dissolution dynamics in recent immigration countries.
Keywords: F22; F66; J61; J12; O31; O32; 330; migration; divorce; marriage market; Italy